The Characteristics of Jangkar Kelud Radio as Disaster Community Radio - Huda, Anam Miftakhul; Bajari, Atwar; Muhtadi, Asep Saeful; Rahmat, Dadang (Jurnal The Messenger, 2018)
This study aims to find out the characteristics of Jangkar Kelud Radio as disaster community radio. The existence of community radio is as information means of disaster mitigation. There are nine Jangkar Kelud community radio stations spread in three regencies of Malang, Blitar, and Kediri. The object of this research is Jangkar Kelud community radio. The method of this research is descriptive qualitative that is the characteristic of Jangkar Kelud Radio is as disaster community radio. The results of this study show the characteristics of community radio is in line with Law No. 32 year 2002. The distinctiveness of Jangkar Kelud community radio are the presence of the radio geographically is in the prone disaster area, the content of on-air and off-air programs is about disaster mitigation, the concept of community radio is by, from and for visible disaster risk reduction through the radio management participation.